2013
DOI: 10.1007/s13762-013-0207-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biodiesel on particulate numbers and composition emitted from turbocharged diesel engine

Abstract: In present study a turbocharged, medium duty compression ignition engine was alternatively fuelled with biodiesel to investigate the changes in particulate matter composition, relative to that taken with diesel fuel. The engine was operated on an AC electrical dynamometer in accordance with an 8-mode, steady-state cycle. The numbers of particles were estimated through electrical low pressure impactor, while sulfates and trace metals were analyzed by ion chromatography and inductively coupled plasma-atomic emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
(40 reference statements)
2
12
0
Order By: Relevance
“…They appear as nitrogenized CN -, C 3 N -, C 5 N -, CNO -, and NO 2 -fragments. Fly ash in exhaust contains mostly transition and alkali earth metals and water-soluble ions produced by inorganic contaminations in lubricating oil and engine wear (Oanh et al, 2010;Popovicheva et al, 2014a;Shah et al, 2014 , which are commonly assigned to pollution of diesel emission (Popovicheva et al, 2014a, b), are observed at relatively small concentrations due to low sulfate abundance in the conventional diesel fuel EN 590 used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They appear as nitrogenized CN -, C 3 N -, C 5 N -, CNO -, and NO 2 -fragments. Fly ash in exhaust contains mostly transition and alkali earth metals and water-soluble ions produced by inorganic contaminations in lubricating oil and engine wear (Oanh et al, 2010;Popovicheva et al, 2014a;Shah et al, 2014 , which are commonly assigned to pollution of diesel emission (Popovicheva et al, 2014a, b), are observed at relatively small concentrations due to low sulfate abundance in the conventional diesel fuel EN 590 used.…”
Section: Discussionmentioning
confidence: 99%
“…The growing concern about their environmental impact and health hazard in urban areas has resulted in the development of modern combustion engines that emit less particulate matter (PM). Concurrently, alternative fuels, such as vegetable oil-based biofuels (referred to as biodiesel), tend to be used in modern combustion engines (Agarwal, 2007;Giakoumis et al, 2012) in an attempt to further lessen soot particles emission and the concentration of unburned hydrocarbons (HC) and carbon monoxide (CO) released in engine exhausts (Dwivedi et al, 2006;Jung et al, 2006;Betha and Balasubramanian, 2011;Shah et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In order to collect the exhaust for the estimation of sub-50 nm and over-50 nm aerosoles, 2 tandem ejector diluters each with a dilution ratio of almost 8:1 were arranged in series, first at 200 °C and then at ambient temperature. The exhaust was then passed through an ELPI (Dekati, Finland) having a corona charger, an electrometer, and a cascade (Shah et al, 2014). A sampling pump was used to provide flow, while the flow rate was controlled by a controller at about 10 L/min.…”
Section: Resultsmentioning
confidence: 99%
“…Biodiesel-diesel blends B20 and B50 have been used to gain a deep insight into the biodiesel role in above discussed emissions. Earlier, authors (Shah et al, 2014) have reported that accumulation mode particles, total TME, and individual elements such as iron and calcium are greatly reduced, while nuclei mode particles and sodium are increased with neat biodiesel (B100). In addition to this, it has also been pointed out that sulphates are slightly, only 8%, increased with B100 as compared to petroleum diesel.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation